1987
DOI: 10.1095/biolreprod36.2.439
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Characteristics of Blastocysts from Spontaneously Ovulating and Gonadotropin-Treated Mice1

Abstract: Differences were found in the surface architecture of blastocysts from spontaneously ovulating and from gonadotropin-treated females of the BALB/cBy and the C57BL/6J strains of mice. Significantly fewer microvilli and a greater percentage of smooth areas were found on the surfaces of blastocysts from gonadotropin-treated females compared to those from spontaneously ovulating females. The differences were greater in blastocysts from gonadotropin-treated immature females than in blastocysts from similarly treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Other studies in agreement with our results presented here have demonstrated that the quality of embryos was affected by superovulation; for example Champlin AK et al [4] showed that blastocysts that developed in vivo in superovulated mice have fewer microvilli on their surface.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies in agreement with our results presented here have demonstrated that the quality of embryos was affected by superovulation; for example Champlin AK et al [4] showed that blastocysts that developed in vivo in superovulated mice have fewer microvilli on their surface.…”
Section: Discussionsupporting
confidence: 93%
“…In vitro studies showed that ovarian stimulation disrupts (Ertzeid & Storeng 1992) Ertzeid & Storeng 2001). Furthermore, analysis of the surface architecture of mouse embryos showed a reduction in the number of cells and of microvilli on blastocysts from gonadotrophin-treated females, compared to those from spontaneously ovulating females (Champlin et al 1987). However, the results of human studies assessing possible effects of ovarian stimulation protocols on embryo development are inconsistent with mouse studies.…”
Section: How Does Ovarian Stimulation Affect Early Oocyte and Embryo mentioning
confidence: 99%
“…However, there is increasing evidence suggesting that ovarian stimulation and the associated high estrogen levels are detrimental on the embryo and associated with a decrease in the fertilization rate. When compared with blastocysts derived from naturally cycling mice, blastocysts that developed in vivo in superovulated mice were found to have fewer microvilli on their surface [170], a reduced [ 35 S]-methionine uptake [171], and a lower cell number and mitotic index [172]. A reduced cell number and a two-fold decrease in viability post-transfer of embryos from gonadotropins-stimulated hamster females, was also observed [21].…”
Section: Part Onementioning
confidence: 99%